MELACAK ALGORITMA HISAB AWAL BULAN QAMARIYAH DALAM KITAB NURUL ANWAR - Ahmad Fauzan (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2014)
This research examines the Risalah al-Falak Nurul Anwar min Muntaha al-Aqwal fi Ma’rifah Hisab al-Sinin wa al-Hilal wa al-Khusuf ala Haqīqī bi al-Tahqīq bi Rasd al-Jadid, the work of KH. Nur Ahmad, SS, using content analysis. The results are: First, the book calculations algorithm in terms of determining the beginning of the month Qamariyah fall under hisab Haqiqi bi al-Tahqīq. While Spherical Trigonometry is the basis for its theory and calculation. Second, in the making process, the book used Badī’ah al-Mitsāl and al-Khulāsah al-Wāfiah as reference. This literature research also found that the trend of the data is taken from the book of Badī’ah al-Mitsāl, while the calculation is taken from the book of al-Khulāsah al-Wāfiah, by adapting the rules of modern astronomy.